EXPLORING THE KNOWLEDGE, ATTITUDE AND BELIEF OF UNIVERSITY STUDENTS REGARDING SUBSTANCE MISUSE (Journal of Forensic Medicine & Toxicology, 2025)
This study explores university students' knowledge, attitudes, and beliefs regarding substance misuse, aiming to identify factors that influence drug use behaviors among youth.
Keywords: Drug Abuse; Knowledge; Attitude; Belief; University Students